Efecto del all-trans ácido retinoico en la producción de citocinas por células mononucleares de sangre periférica (2010)
ABSTRACT: To compare the effect of all-trans retinoic acid in the production of cytokines by peripheral blood mononuclear cells (PBMC) among children with moderate malnutrition (Dn-M), severe (Dn-G) and a control group of children eutrophic (Eu). Methodology: Quasi-experimental research in vitro, to assess the effect of different doses of atRA (0, 17, 30 and 50 nM) on the concentration of cytokines (L-8, IL-1β, IL-6, IL-10, TNF-α and IL-12p70) in PBMC of 21 children, divided into three groups: seven with moderate malnutrition (Dn-M), 7 with severe malnutrition (Dn-G) and 7 healthy children (Eu). Results: Although 71% of malnourished children (Dn-G and Dn-M) showed signs of infection, had a population of leukocytes and lymphocytes lower than the Eu. Children Dn-G reported a concentration of C-reactive protein (CRP), significantly higher than the other two groups and simultaneously younger, shorter (T/E) and lower hemoglobin. The concentration of IL-1β, IL-6, IL-8, TNFα and IL-10 in PBMC was higher in Dn-M than in Dn-G and Eu. Comparison between groups was found that 50 nM of atRA concentration of IL-8 was significantly lower and the higher IL-10 in Dn-G compared with the other two groups. MANOVA analyses indicate these differences were attributed to the fact to belonging the group (Dn-G) and not the dose of atRA (50 nM). Analysis of the effect of different doses of atRA in each group showed a significant decrease with 50nM of atRA of IL-8 in Dn-G and IL-10 in Eu. IL-12p70 increased with doses of 17 nM in Dn-M. Conclusion: atRA affects the production of cytokines but the main determinant of concentration is the type of malnutrition.